Acinetobacter baumannii Efflux Pumps and Antibiotic Resistance - Abdi, Seyyed Naser (Infect Drug Resist, 2020)
Acinetobacter baumannii is a nosocomial pathogen and gram-negative coccobacillus that is responsible for opportunistic infections, pneumonia, and infections of the urinary tract, bloodstream, skin, and soft tissue. This bacterium poses a major public health problem due to inducing resistance to several drugs, isolates, multidrug treatment, and occasionally pan drugs. Drug resistance is not only a major concern caused by A. baumannii but also is considered as the main challenge in many other pathogens. Several factors such as the efflux pump are associated with antibiotic resistance, biofilm production, and genetic mutations. In this review, A. baumannii is introduced in then some of the practical works conducted on the existing efflux pump are reviewed. The importance of the efflux pump is considered in this paper in relation to the antibiotic resistance and mechanisms developed for the inhibition of these pumps as well.